Recent trends in bacteriological and antibiogram profile of isolates from ear, nose and throat in a tertiary care hospital in coastal Karnataka - ., Jyoti; Bhat S., Ravishankara; Srinivasan, Madhumitha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objectives were to study the bacterial pathogens of ear, nose and throat (ENT), to determine the culture and sensitivity pattern of ENT infections in coastal Karnataka. Methods: A retrospective culture and sensitivity profiling study of 109 samples from September 2018 to September 2019 was done in Department of ENT in KVG Medical College and Hospital. Results: Among the pure growth, Pseudomonas aeruginosa was isolated in majority of samples (27.77%) followed by Staphylococcus aureus (22.9%). Klebsiella sp., Acinetobacter sp., Citrobacter, Non enterococcus, Escherichia coli, Proteus sp. and Streptococcus pneumoniae were responsible for remaining samples. Among S. aureus majority was MRSA accounting for 18.51%. P. aeruginosa was most sensitive to amikacin, ceftazidime, meropenem and piperacillin- tazobactam and least sensitive to cotrimoxazole and colistin and most resistant to sparfloxacin, cefaperazone-sulbactam, ceftriaxone-tazobactam and clindamycin. MRSA was most sensitive to gentamicin, amikacin and clindamycin and most resistant to cephalexin, ampicillin and ciprofloxacin. Klebsiella sp. was most sensitive to amikacin and cotrimoxazole and most resistant to sparfloxacin and ceftriaxone. E. coli was most sensitive to gentamicin and cotrimoxazole and most resistant to sparfloxacin. Conclusions: P. aeruginosa, S. aureus and Klebsiella sp. represent majority of culture samples. With ever changing culture & sensitivity pattern and rising antibiotic resistance, a simple step of sending pus samples for the same will help in personalizing the treatment, thereby reducing the disease burden.